Turbulent ambipolar diffusion: numerical studies in two dimensions - Heitsch, F; Zweibel, E; Slyz, A; Devriendt, J (American Astronomical Society, 2004)
Under ideal MHD conditions the magnetic field strength should be correlated with density in the interstellar medium (ISM). However, observations indicate that this correlation is weak. Ambipolar diffusion can decrease the flux-to-mass ratio in weakly ionized media; however, it is generally thought to be too slow to play a significant role in the ISM except in the densest molecular clouds. Turbulence is often invoked in astrophysical problems to increase transport rates above the (very slow) laminar values predicted by kinetic theory. We describe a series of numerical experiments addressing the problem of turbulent transport of magnetic fields in weakly ionized gases. We show, subject to various geometrical and physical restrictions, that turbulence in a weakly ionized medium rapidly diffuses the magnetic flux-to-mass ratio B/ρ through the buildup of appreciable ion-neutral drifts on small scales. These results are applicable to the field strength-density correlation in the ISM, as well as the merging of flux systems such as protostar and accretion disk fields or protostellar jets with ambient matter, and the vertical transport of galactic magnetic fields.